Effects of acute sleep loss on diurnal plasma dynamics of CNS health biomarkers in young men. (17th March 2020) - Benedict, Christian; Blennow, Kaj; Zetterberg, Henrik; Cedernaes, Jonathan
Abstract : Objective: Disrupted sleep increases CSF levels of tau and β-amyloid (Aβ) and is associated with an increased risk of Alzheimer disease (AD). Our aim was to determine whether acute sleep loss alters diurnal profiles of plasma-based AD-associated biomarkers. Methods: In a 2-condition crossover study, 15 healthy young men participated in 2 standardized sedentary in-laboratory conditions in randomized order: normal sleep vs overnight sleep loss. Plasma levels of total tau (t-tau), Aβ40, Aβ42, neurofilament light chain (NfL), and glial fibrillary acidic protein (GFAP) were assessed using ultrasensitive single molecule array assays or ELISAs, in the fasted state in the evening prior to, and in the morning after, each intervention. Results: In response to sleep loss (+17.2%), compared with normal sleep (+1.8%), the evening to morning ratio was increased for t-tau ( p = 0.035). No changes between the sleep conditions were seen for levels of Aβ40, Aβ42, NfL, or GFAP (all p > 0.10). The AD risk genotype rs4420638 did not significantly interact with sleep loss–related diurnal changes in plasma levels of Aβ40 or Aβ42 ( p > 0.10). Plasma levels of Aβ42 (−17.1%) and GFAP (−12.1%) exhibited an evening to morning decrease across conditions ( p < 0.05). Conclusions: Our exploratory study suggests that acute sleep loss results in increased blood levels of t-tau. These changes provide further evidence that sleep loss may have detrimental effects on brain health even in younger individuals. Larger cohorts are warranted to delineate sleep vs circadian mechanisms, implications for long-term recurrent conditions (e.g., in shift workers), as well as interactions with other lifestyle and genetic factors.